Missed opportunity from randomised controlled trials of medical interventions for open-angle glaucoma. Issue 10 (7th March 2017) - Law, Andrew; Lindsley, Kristina; Rouse, Benjamin; Wormald, Richard; Dickersin, Kay; Li, Tianjing
Abstract : Purpose: To evaluate the extent to which intraocular pressure and visual field have been reported as outcomes in randomised controlled trials (also referred to as 'trials') of medical treatments for open-angle glaucoma. Methods: We identified published reports of trials in a systematic review of medical interventions for open-angle glaucoma our group conducted. We assessed whether intraocular pressure and visual field were reported as trial outcomes and classified them to be either completely or incompletely reported for meta-analysis. We also collected data on the length of time patients were followed and source of funding for the trial. Results: As of March 2014, we identified 401 trials that had enrolled 76 861 participants. Eighty per cent of 401 trials provided complete information on intraocular pressure and 11% of the 401 trials provided complete information on visual field. Only a minority of trials followed patients for at least 1 year. About half of all reports in our study stated that receiving funding from the industry. Conclusions: Although the vast majority of trials provided sufficient data for meta-analysis of the effect of medical management of open-angle glaucoma on intraocular pressure, relatively few provided data for analysing the effect on visual field. We considered this as missed opportunity because the data were not available for evidence synthesis. Investigators have an obligation to patients and providers to determine the comparative effectiveness of glaucoma interventions in terms of patient-important outcomes and not to waste data that could have been collected in trials.